The Represenatation of Female Beauty Standard on The Movie "Tall Girl": A Critical Discourse Analysis - Azhari, Firzana Maritza (JALL (Journal of Applied Linguistics and Literacy), 2025)
Representing women's beauty standards in the media significantly shapes people's views on self-esteem. This research is essential to understand how the media reveals a narrow definition of beauty standards. This research analyses the representation of female beauty standard of a main female character on a movie using critical discourse analysis by Sara Mills’ theory. The movie “Tall Girl” served as the data source of this research. The data were analyzed with a qualitative approach through documentation, observation, and note taking and validated by expert judgment to determine the theory of feminism by revealing two research objectives: (1) how is the main female character views the beauty standards from the language used and (2) how is the main female character depicted from the language used in the movie. The findings and discussion of this research revealed that Jodi Kreyman, as the main character, transforms the position of an object of bullying to that of a subject who can accept her physical appearance. In addition, from the reader's position, the film allows the reader to empathize with Jodi's struggle and think more critically about the broader standards of female beauty. In conclusion, the movie challenges narrow beauty standards and demonstrates the importance of self-acceptance. Future research could analyze similar issues or the audience's perspectives on female beauty standards to create new insight.